Necesidad de la creación del recurso de apelación ante la inconstitucionalidad del art 10 de la ley de la jurisdicción contencioso administrativa. - Crespo Aguilera, María José (2014)
The existing legal contradiction between Article 10 of the Law on Administrative Litigation Jurisdiction and Article No. 76. 7 lit. m of the Constitution of the Republic of Ecuador, is manifest, because on one hand the Constitution ensures due process guaranteed by appeal a judgment or settlement in all proceedings in which it is decided on their rights and on the other aside the provisions of the Law of Administrative Jurisdiction which instructs the Administrative Court to hear and determine in a single instance of challenges to regulations, acts and resolutions of the Civil Service, or semi-public person or private law social or public purpose and decide on its legality or illegality. Discard limiting single instance of this Act and create the possibility of a challenge by the well-known appeal, is to run a major proposal, for it is necessary to define concepts such as administrative law, public administration, acts and deeds administrative, and other content in this work, all valid to route to the objective proposed project because you have to understand the origin and purpose of each of these fundamentals to understand why this rule is unconstitutional, especially in response to changes that have been occurring in Public Administration, requiring a connection to other laws, especially with the Constitution of the Republic of Ecuador. So also must confirm this liability to prosecution of administrative jurisdiction of acts and regulations issued by public administrative bodies. The law must address all problems that arise in ensuring consistent access to justice and due process for persons affected in their rights or interests by such acts or provisions, guaranteed by the Constitution of the Republic. This law would be insufficient if it is limited to prosecuting claims deducted in relation to the provisions of the law range below and administrative acts and acts strictly. What really matters is justified and ensure the rights of stakeholders and the general interest, the exact subjection to the law administration in all actions carried out in their capacity as public authority. By law, administrative action is subject to two control means; the administrative procedure and administrative litigation process. Both pathways allow achieving the subordination of the State law, but they have different nature. The administrative authority is the formal ritual of preparation, training, monitoring and challenging the administrative will, however run into a problem that can influence the idea of security as it is the same authority that establishes the procedure to formulate their own will while she herself decides the appeal against his own act or decision. Thus the existence of the Process of Administrative, it is imperative, since whose foundation is the need to subject the actions of government in the opinion of an impartial third party, so that becomes effective the presence of justice in establishing relationships with managed that, and the validity of the legal system in concrete situations, that possibility does not give administrative ensure. It is important to state that under the Modernization Act litigation is not a kind of second instance that would be accessed after attending and exhausted administrative remedies, on the contrary, as if the injured party decides to go straight through the courts this is initiated by putting a claim to jurisdiction in activity in order to resolve a dispute under law. The agreement and subordination of laws under the Constitution should be a fundamental reason why the analysis related to the effective protection, due process, and everything concerning the Administrative Process, additionally with field research, allows an understanding of the topic, located exactly what the legal defect and result in a fair presentation of the legal proposal.